Effects of mechanical wounding and infection patterns of fusarium solani on gaharu formation in Aquilaria malaccensis Lam - Jong, Phai Lee (2012)
Gaharu is the oleoresin found in karas (Aquilaria malaccensis). Recently, many studies have been conducted in order to produce the most suitable and effective inocula in the market. Indeed, there is a need to produce more gaharu in karas tree especially in plantation field. Various fungi have been associated with gaharu formation, however their roles and patterns of colonization are not fully understood. In general, gaharu formation is associated with natural wounding or artificial inoculation by different fungi or chemicals. This study focused on the patterns of Fusarium solani colonization at different wounding time-point via real - time quantitative PCR (qPCR) technique and the effects of artificial inoculation on young karas trees as compared to naturally infected wounded karas in the wild. In addition, artificial inoculation technique with different fungal isolates were also aimed to determine their effects on producing gaharu. This was done by comparing their degree of discoloration formed over a period of 1, 3, 6 months respectively and the chemical constituents. Gaharu compounds produced from both induction methods were identified and compared to commercial samples via GCMS. When tracking the amount of F. solani inocula in two wounded tree over time in the wild, the fungus was found to colonize wounded karas most frequently at the early stage of wounding, often most abundantly during the first 2 weeks. The highest amount of target DNA copies was quantified at 2 weeks in both investigated trees. This indicates that the infection of fungi might take place at the early stage of the wounding process. The decreasing in gene copy number detected in the latter stages, from 6 to 12 months showed that there was no evidence to state that fungi colonized more abundantly in darker wood. In fact, more resins were produced in order to form gaharu. The high level of terpenes were maintained to control the pathogen attacked. The presence of F. solani consistently at every wounding time - point, except for two points in one of the trees, revealed the association of this microbe to gaharu formation. However, its direct role in gaharu formation has to be further investigated, perhaps in a more controlled environment. The study on fungal inoculation was carried out on young 4-year-old trees in a shade house conditions. Trees were harvested at 1, 3 and 6 months after inoculation. The discoloration on the wound and its intensity were measured. ANOVA analysis concluded that the five species of fungal inocula tested were not giving significant differences in terms of discoloration length and intensity. However, the length of discoloration and its intensity increased progressively from pale yellow to dark brown over the time period tested. This implies that time plays an important role for producing gaharu-impregnated wood. When analyzing gaharu compounds using GC-MS, a total of 39 compounds mainly from the group monoterpenes,sesquiterpenes, oxygenated sesquiterpenes, chromone derivatives and fatty acids were identified. Samples analyzed were from commercial gaharu, artificial inoculation and mechanically wounded wood. From GC-MS profiles, all five commercial gaharu, SA, A, B, C and D grades had similar important compounds. Among them were (-)-Aristolene, Palustrol (derivatives of guaiene), γ. Eudesmol, (-)-Aristolene, α-Elemol, Anisylacetone, Benzaldehyde, Benzylacetone, 6-(Benzyloxy)-4, 4-dimethyl-2- chromaone and Agarospirol. When compared to artificial inoculated wood,there were some important fragrant compounds found such as Guaiene, Benzenepropanoic acid,2,5-dimethoxy, Palustrol, Benzylacetone, Benzaldehyde, 6-(Benzyloxy)-4,4-dimethyl-2-chromaone. A new compound of 6-(Benzyloxy)-4,4-dimethyl-2- chromaone was detected in the wood sample and it was also known as 4,4-dimethyl - 6 - phenylmethoxy-3H-chromen-2-one. In overall, the existence of these compounds proved that gaharu was formed in the fungal inoculated wood. This study demonstrated that fungal inoculation could produce gaharu in young trees in just 6 months time. Fungal invasion could be a method to prolong agression since it could indirectly increase resin production. However, this should be tested on a larger scale under field trial conditions.